Designing an E - Commerce Website Based on Wordpress CMS With Payment Gateway Integration at UMKM Asbag Semarang Knitting Bag - Muhammad Farhan Ario Putra; Karnowahadi; Andi Setiawan (Politeknik Negeri Semarang, 2024)
The development of the digital era has forced micro, small and medium enterprises (MSMEs) to develop their marketing strategies. One of the responses made by MSMEs is by utilizing digital platforms such as E-Commerce websites. UMKM Asbag Semarang Knitting Bag is a business that offers products from handmade knitting bags that have unique and attractive choices. This research aims to design an E-Commerce website as an online sales platform by using online payment transactions through Payment Gateway integration and produce an attractive website for Asbag Knitting Bags UMKM in order to gain consumer appeal. The research method used in the research is the Waterfall method which will go through several stage processes such as needs analysis, display design, implementation on the system, testing and website maintenance. The results of the research have been carried out at the testing stage showing that Alpha testing has been tested 100% “Successful”. At the testing stage, Beta testing was also carried out on 40 respondents which showed a percentage of success of 83.6% “Very Good”, besides that beta testing was also carried out on several employees of the Asbag Knitting Bag UMKM which showed a percentage of success of 87.5% “Very Good”. This research is expected to be a solution in answering challenges to be able to improve marketing performance in marketing products on digital platforms. Semakin berkembangnya era digital telah memaksa pelaku usaha mikro, kecil, dan menengah (UMKM) untuk melakukan pengembangan dalam strategi pemasarannya. Salah satu respons yang dilakukan oleh para UMKM yaitu dengan memanfaatkan platform digital seperti website E – Commerce. UMKM Tas Rajut Asbag Semarang merupakan sebuah usaha yang menawarkan produk dari kerajinan handmade tas rajut yang memiliki pilihan yang unik dan menarik. Penelitian ini bertujuan untuk merancang sebuah website E – Commerce sebagai platform penjualan online dengan menggunakan transaksi pembayaran online melalui integrasi Payment Gateway serta menghasilkan website yang menarik untuk UMKM Tas Rajut Asbag agar mendapatkan daya tarik konsumen. Metode penelitian yang digunakan pada penelitian yaitu metode Waterfall yang akan melewati beberapa proses tahapan seperti analisis kebutuhan, desain tampilan, implementasi pada sistem, pengujian dan pemeliharaan website. Hasil penelitian telah dilakukan pada tahap testing menunjukkan bahwa pengujian Alpha telah teruji 100% “Berhasil”. Pada tahap testing juga dilakukan pengujian Beta yang kepada 40 responden yang menunjukkan persentase keberhasilan sebesar 83,6% “Sangat Baik”, selain itu pengujian beta juga dilakukan pada beberapa karyawan UMKM Tas Rajut Asbag yang menunjukkan persentase keberhasilan sebesar 87,5% “Sangat Baik”. Penelitian ini diharapkan mampu menjadi solusi dalam menjawab tantangan untuk dapat meningkatkan kinerja pemasaran dalam memasarkan produk di platform digital.